2007
DOI: 10.1093/imammb/dql021
|View full text |Cite
|
Sign up to set email alerts
|

Disease emergence in multi-host epidemic models

Abstract: Most pathogens are capable of infecting multiple hosts. These multiple hosts provide many avenues for the disease to emerge. In this investigation, we formulate and analyse multi-host epidemic models and determine conditions under which the disease can emerge. In particular, SIS and SIR epidemic models are formulated for a pathogen that can infect n different hosts. The basic reproduction number is computed and shown to increase with n, the number of hosts that can be infected. Therefore, the possibility of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…According to some ecological mathematics models, the presence of multiple hosts increases the possibility of disease emergence (McCormack & Allen 2007). In this study, JABV was identified for the first time in A. paranaensis.…”
mentioning
confidence: 69%
“…According to some ecological mathematics models, the presence of multiple hosts increases the possibility of disease emergence (McCormack & Allen 2007). In this study, JABV was identified for the first time in A. paranaensis.…”
mentioning
confidence: 69%
“…The presence of multiple hosts potentially capable of interspecies disease transmission likely influenced, to some extent, the persistence and distribution of these viruses [1], [28], [60], [61]. This is a key area in the ecology and dynamic of an infectious disease and we acknowledged that the presence of numerous hosts should be one of a key area of future model development.…”
Section: Discussionmentioning
confidence: 99%
“…Spillover events occasionally occur in nature within a geographical region and have been documented for various viruses and sympatric (species occurring in the same geographic region) or syntopic (species sharing the same habitat within the same geographical range) rodent host species, thus providing more evidence that heterologous (secondary) host species are susceptible to infection [9,19,38]. Moreover, multiple host models have indicated that under certain circumstances, persistence of infection within rodent populations can increase with the presence of secondary hosts and spillover [39,40]. Environmental changes that result in greater habitat overlap can create more interspecific encounters that could lead to outbreaks or even the establishment of the viral colonization of a novel host [41].…”
Section: Hantavirus Hostsmentioning
confidence: 99%